UnrealScript game programming all in one - Flynt, John P.; Caviness, Chris (Boston, MA : Thomson Course Technology, 2006)
Written to help you develop the fundamental programming skills you need to immediately begin working with modifications to Unreal Tournament, this book offers approximately 70 starter programs designed as beginner-level workarounds to the Unreal Tournament class hierarchy.
1. The World of UnrealScript Programming 2. Setting Up for Programming 3. Setting Up for Development 4. Setting Up ConTEXT 5. Shell Scripts with ConTEXT 6. Programming the Make.bat File 7. More Function Keys for ConTEXT 8. Refining Your Programming Routine 9. Fundamental UnrealScript Data Types 10. Data Types, Operators, and Operations 11. Built-In Numeric Functions 12. Built-In String Functions 13. Control Statements 14. Repetition Control Statements 15. Arrays 16. Structures and Enumerations 17. Classes and Objects 18. Functions and Classes 19. Classes and Class Associations 20. Associations and Generalizations
Includes index.
Keywords: Computer games -- Programming; UnrealScript (Computer program language)